Symbiotic Relationship between Human and Non-human: A Deep Ecological Reading of The Wonderful Wizard of Oz - Sharma, Kamal; Joshi, Amrit Prasad (Pragnya Sarathi, 2026)
This paper explores a symbiotic relationship between the human and non-human from a deep ecological perspective in The Wonderful Wizard of Oz. Drawing on the concept of deep ecology developed by Arne Naess, the paper examines how symbiotic relationship based on deep ecological principle contributes for every living creature or being echoing the theme of equal intrinsic worth of every living being. As seen in the novel, Dorothy’s bond with Toto, her friendship with Tin Man, the Cowardly lion, and the Scarecrow show the symbiosis. Her attachment to the natural world seen in her association to Kansas prairie, Emerald City, grassland is a part of biospherical issue. Scarecrow’s brainlessness proves to be wiser than academic credentialities. Tin Woodman’s heartlessness demonstrates greater compassion. And the Lion’s cowardliness hints at its bravery. The issue of complexity in simplicity is seen in the cyclone as a chaotic natural force that generates narrative order. Arne Naess’s deep ecology gives an emphasis on the relationship between animals which can be seen in the harmonious relation between Toto (also called dog) and cowardly lion in The Wonderful Wizard of Oz. Similarly, the relation between the material environments Kansas Prairies, Emerald city, Poppy field exhibits material environment, and the objects hinting technologies like the silver shoes and the balloon show how life is happy for every creature. In the similar fashion, the weather phenomenon indicated by the cyclone as narrative engine shows benevolent nature of nature. There is mutual benefit in the symbiotic relation as envisioned by Arne Naess.